2008
DOI: 10.2214/ajr.07.2796
|View full text |Cite
|
Sign up to set email alerts
|

Incidental Enchondromas of the Knee

Abstract: Incidental enchondromas can be identified on 2.9% of routine MR knee examinations, most frequently in the distal femur (2.0%). This significant prevalence is much higher than in an autopsy series (0.2%), likely reflecting the increased sensitivity of MRI for detecting small lesions, and is important to recognize to avoid confusion with other pathologic entities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
73
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 7 publications
2
73
1
2
Order By: Relevance
“…The prevalence of incidentally found enchondromas in the present study (3.3%) was, therefore, compatible with data in the literature. In the present study, the prevalence of enchondromas in the distal femur (2.4%) was slightly higher than the prevalence observed by Walden et al (13) . Enchondromas may also be incidentally found with a relative frequency at routine shoulder studies (2.1%), in most of times located in the contiguous region of the physis (26) .…”
Section: Discussioncontrasting
confidence: 81%
See 4 more Smart Citations
“…The prevalence of incidentally found enchondromas in the present study (3.3%) was, therefore, compatible with data in the literature. In the present study, the prevalence of enchondromas in the distal femur (2.4%) was slightly higher than the prevalence observed by Walden et al (13) . Enchondromas may also be incidentally found with a relative frequency at routine shoulder studies (2.1%), in most of times located in the contiguous region of the physis (26) .…”
Section: Discussioncontrasting
confidence: 81%
“…According to Walden et al, the prevalence of incidentally found enchondromas at knee MRI was of 2.9%, most of times located in the distal femur (2.0%) (13) . In the study of Walden et al, the prevalence of lesions in the distal tibia corresponded to 0.7%, and 0.2% in the fibula.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations